MENINGKATKAN HASIL BELAJAR SEPAKBOLA MELALUI PERMAINAN GAWANG TONG PADA SISWA KELAS V SDN 81/II MUARA BUNGO - Silis Silis (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2018)
The background of the problem of this research is the lack of proper learning and inadequate facilities in the process of football learning and the lack of mastery of technical skills, the basis of soccer games, so that student learning outcomes are less optimal. Therefore, the purpose of this study is to increase the activity and results of learning football through tong goal play. This study uses a class action research method. The subjects in this study were fifth grade students of SDN 81 / II Muara Bungo. The number of subjects in this study were 36 students. The meeting in this study was designed in two cycles, namely cycle I and cycle II. The instruments used in retrieving data were obtained from the results of the performance tests displayed by students during the test. The results of this study indicate that through the goalpost game can improve students' abilities in soccer learning. In the first cycle, it was known that the percentage of learning completeness was 68% with a total of 25 students, experiencing an increase in the second cycle of 77%, with the total completeness of 29 students. The conclusion of this study is that the approach of playing football with the goalpost can improve football's ability in fifth grade students of SDN 81 / II Muara Bungo. The suggestion of this study is aimed at the Penjasorkes teachers who have difficulty in improving the learning outcomes of football, this CAR can be used as input to overcome the problem.